Zygomatic abscess with temporomandibular joint effusion complicating acute otitis media - Kaya, Hanifi; Vural, Alperen; Somdaş, Mehmet Akif; Öztürk, Mustafa; Doğan, Murat (Aves, 2016)
The incidences of extracranial and intracranial complications of acute otitis media (AOM) in children have markedly decreased in the postantibiotic era. Zygomatic abscesses are the rarest type of abscesses originating from mastoiditis. This paper presents a case with a zygomatic abscess as a complication of acute coalescent mastoiditis in a 7-year-old girl who underwent cortical mastoidectomy and myringotomy-ventilation tube insertion.
WOS: 000386676300007
Keywords: Acute Otitis Media; Complications; Subperiosteal Abscess; Zygomatic Abscess